HYBRID AND INBRED RICE VARIETIES HAVING HIGH RATOONING ABILITY IN TIDAL SWAMPLAND - Susilawati Susilawati; Bambang Sapta Purwoko (Indonesian Agency for Agricultural Research and Development, 2018)
Tidal swampland in Indonesia is potential for cultivation of inbred and hybrid rice. However, rice cultivation in this land can be done only one time annually. Rice cultivation with ratoon system in this land might increase production from both the main crop and their ratoon. The study aimed to evaluate the ability of hybrid and inbred rice to produce ratoon and their grain yield in the tidal swampland of Central Kalimantan. The experiment was arranged in a randomized block design with 12 rice varieties as treatments, namely six hybrids (Hipa 3, Hipa 4, Hipa 5, Hipa 6, Maro and Rokan) and six inbreds (Batanghari, Ciherang, IR42, Margasari, Mekongga and Sintanur); replicated three times. Cultivation of the main crop followed the recommendation. At harvest, the main crops were cut at 20 cm from the ground and fertilized with 100 kg ha-1 urea. The results showed that ratoon crops were emerged at 5–6 days after cutting, with 2–4 leaves per panicle and 5.5–26.0 tillers per clump. Average harvesting age of the ratoon was 69 days. Ratoon yield of the hybrids was better than that of the inbreds; the average was 75.2% of the main crops. Based on the criteria of rice yield, three clusters were identified, i.e. high (>2 t ha-1): Hipa 3, Hipa 4, Hipa 5, Maro, Rokan, Ciherang and Sintanur; medium (1–2 t ha-1): Hipa 6, IR42, Margasari and Mekongga, and low, Batanghari. The study suggests that hybrid varieties could be developed in tidal swamplands.